Profitability of the banking sector in the Euro area : a panel regression analysis after the Global Financial Crisis - Küsters, Malte Maximilian (2020)
The present Dissertation evaluates the impact of Asset-Backed Securities (A.B.S.) on the largest U.S. commercial banks during the subsequent stage of the U.S. business cycle in the aftermath of the U.S. ‘Subprime’ crisis. This analysis covers the 14 largest U.S. commercial banks during the period of September 2009 through December 2018. The followed approach regresses the total risk from each bank, measured as total excess equity returns’ volatility, on both systematic and unsystematic risk, while controlling for size, leverage, and macroeconomic effects. This research presents new empirical evidence on the effects of securitization on systematic risk, given there is no consensus amongst the scientific literature concerning these effects. This Dissertation’s findings suggest that asset-backed securitization and banks’ systematic risk are negatively correlated for the period and bank sample considered. Moreover, this research produces robust results replicable to distinct timespans and adjusted samples. Finally, no evidence is found of asset-backed securitization (excluding mortgage-backed securitization) positively affecting banks’ unsystematic risk.